Quality of life diabetes mellitus: definitions, modern research approaches, tool for evaluation - Yulia Andreevna Shishkova; Oleg Gennad'evich Motovilin; Elena Viktorovna Surkova; Alexander Yur'evich Mayorov (Сахарный диабет)
Quality of life (QoL) studies are very important in many chronic diseases. Diabetes srongly impacts on QoL because of complex control and treatmentregiments and multiple somatic symptoms (acute and chronic complications). In turn, QoL has a significant impact on the prognosis of the disease.The paper reviws QoL definitions, evaluation approaches in medicine, list of examination tools.